Potential of a Quorum Quenching Bacteria Isolate Ochrobactrum intermedium D-2 Against Soft Rot Pathogen Pectobacterium carotovorum subsp. carotovorum - Fan, Xinghui; Ye, Tian; Li, Qiting; Bhatt, Pankaj; Zhang, Lianhui; Chen, Shaohua (Frontiers in Microbiology, 2020)
Quorum quenching (QQ) is a promising strategy for preventing and controlling quorum sensing (QS)-mediated bacterial infections. It interferes with QS by the inhibition of signal synthesis, the detection of enzyme-catalyzed degradation, and the modification of signals. N-Acyl homoserine lactones (AHLs) represent a family of widely conserved QS signals involved in the regulation of virulence factor production in many Gram-negative bacterial pathogens. In this study, AHL-degrading bacterial strains were isolated, and the most efficient one was evaluated for its potential against QS-mediated pathogens. Results showed that an AHL-degrading bacteria Ochrobactrum intermedium D-2 effectively attenuated maceration produced by the pathogen Pectobacterium carotovorum subsp. carotovorum (Pcc) on radish and potato slices. Strain D-2 exhibited a superior AHL degradation activity and efficiently degraded various AHLs, including N-hexanoyl-L-homoserine lactone (C6HSL), N-(3-oxohexanoyl)-L-homoserine lactone (3OC6HSL), N-(3-oxooctanoyl)-L-homoserine lactone (3OC8HSL), and N-(3-oxododecanoyl)-L-homoserine lactone (3OC12HSL). Analysis of the degradation products of AHL by gas chromatography-mass spectrometry led to the identification of N-cyclohexyl-propanamide and propanamide as the main intermediate products, suggesting that AHL was degraded by hydrolysis. Annotation and analysis of the whole genome sequence of strain D-2 revealed the presence of an AHL-lactonase, termed AidF. Moreover, the application of strain D-2 was able to substantially reduce the disease severity caused by Pcc on host plants. These results reveal the biochemical basis of a highly efficient AHL-degrading bacterial isolate and present the potential to attenuate Pcc virulence through QQ.